2004
DOI: 10.1002/elps.200406096
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized microfluidic enzymatic reactors

Abstract: The use of enzymes for cleavage, synthesis or chemical modification represents one of the most common processes used in biochemical and molecular biology laboratories. The continuing progress in medical research, genomics, proteomics, and related emerging biotechnology fields leads to exponential growth of the applications of enzymes and the development of modified or new enzymes with specific activities. Concurrently, new technologies are being developed to improve reaction rates and specificity or perform th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(143 citation statements)
references
References 105 publications
(103 reference statements)
0
142
0
1
Order By: Relevance
“…This bioencapsulation strategy therefore provides an economical and rapid route for synthesizing IMER systems with a number of advantages including; minimal preparation time, high immobilization efficiency and excellent stability. IMERs could be designed to contain an enzyme for biocatalysis or organic synthesis, for rapid screening in medical diagnostics and therapy or for developing IMER columns for affinity chromatography [1,2,25]. In addition, coimmobilization of multienzyme systems is also possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bioencapsulation strategy therefore provides an economical and rapid route for synthesizing IMER systems with a number of advantages including; minimal preparation time, high immobilization efficiency and excellent stability. IMERs could be designed to contain an enzyme for biocatalysis or organic synthesis, for rapid screening in medical diagnostics and therapy or for developing IMER columns for affinity chromatography [1,2,25]. In addition, coimmobilization of multienzyme systems is also possible.…”
Section: Resultsmentioning
confidence: 99%
“…Immobilized enzyme reactors (IMERs) have found application in catalysis and have also been used with a wide variety of receptor proteins for substrate interaction and inhibition studies [1][2][3][4][5][6][7]. The main advantages of immobilized enzyme systems are stability and reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices can address the future analytical needs of increased throughput, lower sample and reagent consumption, smaller size, and lower operating costs [3]. It has been found that microfluidic-based enzymatic reactors can carry out protein digestion with high efficiency to facilitate subsequent reliable protein identification by peptide mass fingerprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Recent significant developments incorporate immobilization of enzymes on the surfaces of suitable carrier materials. Immobilization can be done by: covalent attachment to the activated support, • physical adsorption of the protein onto a solid matrix, and • copolymerisation of the protein with the polymers [64]. • Attaching enzymes to a microreactor wall is a limiting step for using enzymes in this type of microstructured reactors.…”
Section: Enzymes In Microreactorsmentioning
confidence: 99%